2019
DOI: 10.1051/0004-6361/201834426
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission of z > 2.5 active galactic nuclei can be obscured by their host galaxies

Abstract: We present a multi-wavelength study of seven AGN at spectroscopic redshift > 2.5 in the 7 Ms Chandra Deep Field South, selected to have good FIR/sub-mm detections. Our aim is to investigate the possibility that the obscuration observed in the X-rays can be produced by the interstellar medium (ISM) of the host galaxy. Based on the 7 Ms Chandra spectra, we measured obscuring column densities N H, X in excess of 7 × 10 22 cm −2 and intrinsic X-ray luminosities L X > 10 44 erg s −1 for our targets, as well as equi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
66
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 134 publications
15
66
4
Order By: Relevance
“…This selection returns six targets spanning the redshift range ∼ 2.5 -4.8. This sample includes six of the seven sources studied by Circosta et al (2019), who adopted our same selection criteria except for the requirement of heavy obscuration. As pointed out by those authors, the fact that the FIR detection criterion is sufficient to select only obscured AGN indicates a connection between the SF-heated dust in the ISM that is responsible for the FIR to (sub)millimeter emission and the nuclear absorption.…”
Section: Sample Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…This selection returns six targets spanning the redshift range ∼ 2.5 -4.8. This sample includes six of the seven sources studied by Circosta et al (2019), who adopted our same selection criteria except for the requirement of heavy obscuration. As pointed out by those authors, the fact that the FIR detection criterion is sufficient to select only obscured AGN indicates a connection between the SF-heated dust in the ISM that is responsible for the FIR to (sub)millimeter emission and the nuclear absorption.…”
Section: Sample Selectionmentioning
confidence: 99%
“…This result was later confirmed by Mainieri et al (2005) who also reported a submillimeter detection at 850 µm using SCUBA. Exploiting high resolution (∼0.2") ALMA observations, Circosta et al (2019) found that the single object associated with XID 337 in the Spitzer/MIPS, Herschel and SCUBA maps is actually a blend of two sources, whose emission is dominated by a bright QSO at 3.5" separation; thus, the Mid-IR/Far-IR photometric datapoints of XID 337 were converted into upper limits. XID 551 was the first type II AGN ever detected in the CDF-S 1-Ms exposure at z>3 (Norman et al 2002), for which Comastri et al (2011) found a large column density (log N H > 23) performing an Xray spectrum analysis using 3.3-Ms XMM-Newton survey data.…”
Section: Sample Selectionmentioning
confidence: 99%
See 3 more Smart Citations